2021
DOI: 10.1002/smll.202007242
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Functional Groups Containing N, S, and O on Graphene Surface for Stable and Fast Charging Li‐S Batteries

Abstract: Lithium‐sulfur (Li‐S) batteries are considered one of the most promising energy storage technologies, possibly replacing the state‐of‐the‐art lithium‐ion (Li‐ion) batteries owing to their high energy density, low cost, and eco‐compatibility. However, the migration of high‐order lithium polysulfides (LiPs) to the lithium surface and the sluggish electrochemical kinetics pose challenges to their commercialization. The interactions between the cathode and LiPs can be enhanced by the doping of the carbon host with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Thermogravimetry can be used to test the thermal stability of materials [ 62 , 63 ]. The TGA curves comparison between cubic calcium carbonate, spherical calcium carbonate and the composite material are shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermogravimetry can be used to test the thermal stability of materials [ 62 , 63 ]. The TGA curves comparison between cubic calcium carbonate, spherical calcium carbonate and the composite material are shown in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The second weight loss between 610 °C and 790 °C is due to undecomposed, so the weight loss rate is only about 34.8~35.7%. Thermogravimetry can be used to test the thermal stability of materials [62,63]. The TGA curves comparison between cubic calcium carbonate, spherical calcium carbonate and the composite material are shown in Figure 6.…”
Section: Structure and Crystal Typementioning
confidence: 99%
“…For the co‐existence of doped atoms and compounds in cathode material, it has been proved that the presence of doped atoms (such as N, S, O) on the surface of carbon substrate can boost the interaction between various Li 2 S n and the electrode surface, or improve the interface properties of compounds and polysulfides. This strategy not only ensures the uniform growth of the polar compounds on the surface of the substrate but also further enhances the catalytic effect to suppress the shuttle effect and improve the poor redox kinetics [94,95] . Yang et al [96] .…”
Section: Doping Strategiesmentioning
confidence: 99%
“…For example, we found that the interlayer distance of GO increase to 8.9 Å from 6.5 Å after intercalation of one layer of acetonitrile molecules, and expand to 12.7 Å with the intercalation of another layer of solvent molecules, and further increase to 16.4 Å after the co-intercalation of ions [ 28 ]. In addition, we also demonstrated that the addition of molecules (e.g, aminobenzene) with a larger size than solvent molecules and ions results in an enlarged interlayer distance with permanent size [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%